LOFAR discoveryof radio emission in MACS J0717.5+3745. Issue 3 (15th May 2018) - Bonafede, A; Brüggen, M; Rafferty, D; Zhuravleva, I; Riseley, C J; van Weeren, R J; Farnes, J S; Vazza, F; Savini, F; Wilber, A; Botteon, A; Brunetti, G; et al.
ABSTRACT: We present results from Low-Frequency Array (LOFAR) and Giant Meterwave Radio Telescope (GMRT) observations of the galaxy cluster MACS J0717.5+3745. The cluster is undergoing a violent merger involving at least four sub-clusters, and it is known to host a radio halo. LOFAR observations reveal new sources of radio emission in the Intra-Cluster Medium: (i) a radio bridge that connects the cluster to a head-tail radio galaxy located along a filament of galaxies falling into the main cluster, (ii) a 1.9 Mpc radio arc that is located north-west of the main mass component, (iii) radio emission along the X-ray bar that traces the gas in the X-rays south-west of the cluster centre. We use deep GMRT observations at 608 MHz to constrain the spectral indices of these new radio sources, and of the emission that was already studied in the literature at higher frequency. We find that the spectrum of the radio halo and of the relic at LOFAR frequency follows the same power law as observed at higher frequencies. The radio bridge, the radio arc, and the radio bar all have steep spectra that can be used to constrain the particle acceleration mechanisms. We argue that the radio bridge could be caused by the re-acceleration of electrons by shock waves that are injected along the filament during the cluster mass assembly. Despite the sensitivity reached by our observations, the emission from the radio halo does not trace the emission of the gas revealed by X-ray observations. We argue that this could be due to the difference in the ratio of kinetic over thermal energy of the intra-cluster gas, suggested by X-ray observations.